Аналіз роботи теплового насосу в системі низькотемпературної ректифікації суміші пропан-бутан - Морозюк, Лариса Іванівна; Костенко, Євген Володимирович (Національний технічний університет "Харківський політехнічний інститут", 2021)
В роботі представлений аналіз роботи теплового насосу в системі низькотемпературної ректифікації суміші пропан-бутан, що можна розглядати як початок теоретичного дослідження одноступеневих компресорних теплових насосів в малих системах низькотемпературної ректифікації суміші вуглеводнів. Пропан високої чистоти отримують з суміші пропан-бутан низькотемпературною ректифікацією. Вирішуючи завдання енергозбереження запропоновано систему «ректифікаційна колона – тепловий насос», який трансформує тепло, відведене при охолодженні «отдувки» у тепло, що поглинається при нагріванні кубового залишку. Аналіз роботи теплового насосу оцінено з позицій термодинаміки – методом енергетичного аналізу циклу з різними робочими речовинами, і техніки – встановлення впливу інженерних факторів на характеристики системи. Встановлено переваги пропану як робочої речовини теплового насосу в системі ректифікації суміші пропан-бутан.

The article presents the results of the analysis of the operation of a heat pump in the system of low-temperature rectification of a propane-butane mixture. High-purity propane is obtained from a propane-butane mixture. A "rectification column-heat pump" system is proposed, which transforms the heat removed during the cooling of the component in the upper part of the column into heat absorbed during heating of the bottoms. In accordance with the energy balance of the system, it has been established that part of the heat pump condensation is not used in the distillation column, but is removed to the environment. The heat pump flow diagram contains one evaporator and two condensers. The operation of the heat pump is evaluated from the standpoint of thermodynamics – by the method of energy analysis of the cycle with R134 and R290 working substances, It has been established that the low thermodynamic efficiency of the heat pump is determined by external irreversible losses in the condensers and the evaporator The advantages of R290 as a working substance of the heat pump have been proved and the required theoretical volumetric capacity of the compressor has been determined.
Analysis of the heat pump operation in the low-temperature rectification system of propane-butane mixture
Keywords: термодинамічний аналіз; режими роботи; thermodynamic analysis; operating modes